Strengthening Forest Governance in Ethiopia through Integrated Geospatial Analysis and Inclusive Institutional Reform - Shabu Jemal Abakorma (no, 2026)
Ethiopia’s forests are vital for climate resilience, biodiversity, and livelihoods, yet remain threatened by weak enforcement, institutional fragmentation, and inadequate monitoring. This brief proposes actionable reforms: institutionalizing local policy performance evaluation, integrating geospatial tools into governance, and improving cross-sectoral coordination. It introduces Community-Based Forest Heritage Hubs to pilot agro-ecotourism, linking community stewardship to sustainable revenue. Prioritizing transparency and inclusion will align forest management with national climate goals and equitable development. Strengthening institutions, technology, and community collaboration will secure Ethiopia’s forests as pillars of sustainable development. This policy brief uniquely integrates geospatial forest monitoring, institutional performance evaluation, and community-based nature enterprises into a single governance framework tailored to Ethiopia’s forest–climate–livelihood nexus.
Forest policy brief
has no
Keywords: Forest governance; Ethiopia; geospatial analysis; policy integration; community adaptation; sustainable development.